The Impact of Organizational Climate and Perceived Organizational Support on Organizational Commitment: The Mediating Role of Job Satisfaction - Hari, Minti; Astuti, Herni Justiana; Tubastuvi, Naelati; Fakhruddin, Iwan (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to analyze the influence of organizational climate, perceived organizational support, and job satisfaction on Organizational Commitment. The analysis uses Structural Equation Modeling with the Partial Least Square (PLS) approach. The population in this study were all employees at the Cilacap Regency Regional Hospital except doctors and structural officers with a total sample of 273 people. The main findings of this research show that perceived organizational support has a positive effect on job satisfaction, but organizational climate has no effect. Organizational climate and job satisfaction have a positive effect on organizational commitment, but perceived organizational support has no effect. Job satisfaction can mediate the relationship between perceived organizational support and organizational commitment; however, job satisfaction cannot mediate the relationship between organizational climate and commitment.